Hypogammaglobulinemic sprue manifested as chronic intestinal failure: An uncommon but effective indication for home parenteral nutrition - Gonçalo Nunes; Cláudio Martins; Cristina Teixeira; Miguel Fróis Borges; Ana Paula Oliveira; Jorge Fonseca (Turkish Journal of Gastroenterology, 2019)
Cite this article as: Nunes G, Martins C, Teixeira C, Fróis-Borges M, Oliveira AP, Fonseca J. Hypogammaglobulinemic sprue manifested as chronic intestinal failure: An uncommon but effective indication for home parenteral nutrition. Turk J Gastroenterol 2018; 29: 717-8.